Mind wandering in adults with attention deficit hyperactivity disorder: Preliminary evaluation using the Mind Excessively Wandering Scale in a Japanese clinical population. Issue 2 (23rd June 2022) - Hayashi, Wakaho; Tomita, Akisa; Iwanami, Akira
Abstract: Aim: Mind wandering (MW) has been closely associated with attention deficit hyperactivity disorder (ADHD); however, the field remains understudied in Japan. The present study examined MW in adults with ADHD using the Mind Excessively Wandering Scale (MEWS) in a Japanese clinical population. Methods: Fifty‐two adults with ADHD (mean age, 33.0 years; 33 men), diagnosed per the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM‐5) criteria, completed the MEWS, Mind Wandering Questionnaire, Conners' Adult ADHD Rating Scale (CAARS), Autism Spectrum Quotient (AQ), and Japanese Adult Reading Test‐25. Results: The mean MEWS score was 18.8 (standard deviation, 7.6). MEWS scores showed significant correlations with the CAARS Inattention/Memory Problems, Problems with Self‐Concept, DSM‐IV ADHD Symptoms Total, ADHD Index, and AQ scores. Higher MEWS scores were associated with greater ADHD and autism spectrum disorder symptoms in patients with ADHD. Conclusion: Our results not only provide supporting evidence of the presence of excessive MW in adults with ADHD, but also indicate the heterogeneous nature of MW in ADHD. Abstract : Mind wandering in adults with ADHD was examined using the Mind Excessively Wandering Scale (MEWS). Adults with ADHD showed an elevated level of mind wandering and higher MEWS scores were associated with greater ADHD and autism spectrum disorder symptoms.